Orbital Angular Momentum Optical Amplifier Based on PbS-Doped Ring-Core Fiber - Xu, Lingmin; Shang, Yana; Yang, Jinhong; Chen, Zhenyi; Pang, Fufei; Liu, Huanhuan; Dong, Yanhua; Chen, Na; Wen, Jianxiang; Wang, Tingyun (Frontiers in Physics, 2020)
A unique orbital angular momentum (OAM) optical amplifier based on ring-core fiber doped with lead sulfide (PbS) is realized for the first time in this study. The PbS-doped ring-core fiber is fabricated by using the method of modified chemical vapor deposition. The cross-sectional microscope image of the fiber is obtained, and the difference in the refractive index between the ring core and the cladding of the fiber, measured by a three-dimensional refractive-index tester, reached 1%. The content of sulfur and lead in the ring core of the PbS-doped ring-core fiber is confirmed by energy spectrum analysis. The first order OAM optical amplifier based on PbS-doped ring-core fiber is built. The experiment confirms that the air-hole PbS-doped ring-core fiber can support the OAM |l|=1 modes. In addition, 2.3 dB of on–off gain is obtained for the OAM |l|=1 mode at 1550 nm. Its fluorescence spectrum ranges from 1100 to 1600 nm using the backward pumping method.